Morphology and identification of the mature larvae of several species of the genus Otiorhynchus (Coleoptera, Curculionidae, Entiminae) from Central Europe with an update of the life history traits - Gosik, Rafał; Sprick, Peter; Skuhrovec, Jiří; Deruś, Magdalena; Hommes, Martin (Zootaxa, 2016)
The mature larvae of 14 Otiorhynchus taxa are described: O. (Otiorhynchus) armadillo (Rossi, 1792), O. (Nehrodistus) armatus Boheman, 1846, O. (Otiorhynchus) aurifer Boheman, 1843, O. (Pocodalemes) crataegi Germar, 1824, Otiorhynchus (Arammichnus) indefinitus Reitter, 1912 (syn. O. dieckmanni Magnano, 1979), O. (Choilisanus) raucus (Fa-bricius, 1777) and 3 taxa of the O. (Otiorhynchus) tenebricosus complex (Herbst, 1784), O. (Otiorhynchus) clavipes (Bonsdorff, 1785), O. (Otiorhynchus) fuscipes (Olivier, 1807) and O. (Otiorhynchus) lugdunensis Boheman, 1843, are described and illustrated for the first time. The larvae of (Otiorhynchus) meridionalis Gyllenhal, 1834, O. (Pendragon) ovatus (Linnaeus, 1758), O. (Zustalestus) rugosostriatus (Goeze, 1777), O. (Metopiorrhynchus) singularis (Linnaeus, 1767), and O. (Dorymerus) sulcatus (Fabricius, 1775) are redescribed and illustrated, and new characters are added. Important characters of the mature larvae (e.g. chaetotaxy, shape of head and body) are explained in detail and illustrated. A key to the identification of the mature larvae of 19 Otiorhynchus taxa is provided. Breeding and collecting data of the larvae are given, and the study is completed by a current overview on the life histories of all treated species.